P5.069 Copan ESwab™, a Liquid Based Microbiology Device, Can Be Used For the Preservation of Neisseria Gonorrhoeae For Culture and For Detection of CT/NG by Gen-Probe ® APTIMA ® COMBO 2 Assay. (13th July 2013) - Jett-Goheen, M; Barnes, M; Duncan, D; Quinn, N; Ghanem, K; Gaydos, C
Abstract : Background: Copan Liquid Amies Elution Swab (ESwab™) Collection and Transport System incorporates maintenance medium which can sustain the viability of Neisseria gonorrhoeae (NG). Swab specimens placed in the tube and stored at room temperature (RT°) can be cultured within 24 hours, and aliquots for nucleic acid amplification tests (NAATs) can be processed within five days. Methods: Clinicians at a Baltimore City Health Department STD clinic used standard-of-care aluminium shaft swabs with polyester tips to collect urethral swabs from men, smeared a slide for Gram stain, and placed NG positive (by smear) swabs into investigational ESwab™ tubes. The ESwab™ collection swab applicator was then broken off into the tube and the cap was closed. Culture was performed after tube sat from 5 to 28 hours at RT°. Tube was vortexed for 5 seconds; 100 μl was inoculated to MTM plate, streaked for isolation, and incubated in appropriate conditions for 48–72 hours; 100 μl was placed into Gen-Probe ® Unisex transport tube for testing by APTIMA ® COMBO 2 assay. Results: Of 35 swabs, 26 (74%) were culture positive for presumptive NG (Gram negative diplococci, oxidase positive). Colony counts ranged from 1 to > 500 colonies. 35 (100%) swabs were positive for NG by Gen-Probe ® APTIMA ® COMBO 2 assay. Six (17%) were also positive for Chlamydia trachomatis (CT) by Gen-Probe ® assay. Conclusion: Although quality of collected clinical specimen and quantity of NG on the swab are significant variables in obtaining reliable culture results, the ESwab™ System was able to maintain NG viability for at least 24 hours, and stabilised nucleic acids for Gen-Probe ® testing. The ability to maintain culture viability of NG up to 24 hours until NAAT testing is completed could eliminate the necessity to perform cultures on all patients who are being screened for NG, with cultures maintained only for susceptibility testing for NAAT+ patients.